Meningkatkan Hasil Belajar Matematika Dengan Model Pembelajaran Problem Based Learning Berbantuan Media Kartu Bilangan Pada Siswa Kelas 2 - Berlian Pratama; llham Yudha Perwira; Agus Winarto; Iqbal Fikry Ramadhan; Melik Budiarti (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aimed to improve the mathematics learning outcomes of second-grade students at SD Negeri 01 Klitik on addition and subtraction through the implementation of the Problem-Based Learning (PBL) model assisted by number card media. The study employed a qualitative approach using Classroom Action Research (CAR), conducted in two stages: the pre-cycle and Cycle I, consisting of planning, action, observation, and reflection. The participants were 16 second-grade students. Data were collected through tests, observations, and documentation, and analyzed descriptively using learning mastery percentages and classroom activity data. The findings revealed that the implementation of the Problem-Based Learning model assisted by number card media significantly improved students' mathematics learning outcomes. In the pre-cycle stage, the average score was 71.19, with a learning mastery rate of 18.75% (3 out of 16 students). After the implementation of the intervention in Cycle I, the average score increased to 80.56, while the learning mastery rate rose to 93.75% (15 out of 16 students). In addition, teacher activity reached 99%, and student activity achieved 95%, both categorized as very good. These findings indicate that the Problem-Based Learning model supported by number card media is effective in improving mathematics learning outcomes, student engagement, and numeracy skills among second-grade elementary school students in addition and subtraction lessons.